2011
DOI: 10.1212/wnl.0b013e31820c2ebd
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex inhibition

Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) is a childhood-onset behavioral diagnosis in which children often fail to meet age norms in development of motor control, particularly timed repetitive and sequential movements, motor overflow, and balance. The neural substrate of this motor delay may include mechanisms of synaptic inhibition in or adjacent to the motor cortex. The primary objective of this study was to determine whether transcranial magnetic stimulation (TMS)-evoked measures, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 37 publications
9
120
0
2
Order By: Relevance
“…Supportive evidence for this framework also comes from recent transcranial magnetic stimulation (TMS) studies revealing reduced M1 cortical inhibition in children with ADHD (Gilbert et al, 2011; Wu et al, 2012). Our finding that increased motor overflow is associated with decreased extent of neural activation in M1 contralateral to the voluntary movement likely reflects dendritic activity, as increased overflow movements would be expected to be associated with increased firing of pyramidal cells in M1.…”
Section: Discussionmentioning
confidence: 90%
“…Supportive evidence for this framework also comes from recent transcranial magnetic stimulation (TMS) studies revealing reduced M1 cortical inhibition in children with ADHD (Gilbert et al, 2011; Wu et al, 2012). Our finding that increased motor overflow is associated with decreased extent of neural activation in M1 contralateral to the voluntary movement likely reflects dendritic activity, as increased overflow movements would be expected to be associated with increased firing of pyramidal cells in M1.…”
Section: Discussionmentioning
confidence: 90%
“…Applying a rate of spontaneous eye blinks, the acoustic startle eye blink response (ASER), and motor lack of persistence, Tantillo et al (2002) observed an interaction between sex and exercise intensity, with induced improvements that were not explained by physical fitness, activity history, or selected personality attributes after following maximal/submaximal exercise in 8-12-year-old ADHD boys and girls. In the case of cognitive domains, there are consistent deficits in behavioral inhibition (Casey et al 1997;Gilbert et al 2011), attention regulation (Arnsten and Pliszka 2011), working memory (Beck et al 2010;Martinussen et al 2005), planning (Chamberlain et al 2011Scheres et al 2010), and motor coordination (Chan et al 2010;Ghanizadeh, 2010). Physical exercise appears to improve performance in both cognitive and motor domains of disorder, whether in patients or healthy controls: In order to test the hypothesis that physical activity may be particularly beneficial for ADHD children, Gapin et al (2011) have reviewed the evidence supporting that hypothesis and have provided preliminary results from 16 ADHD volunteers who performed the neuropsychological tasks prior to and following a treatment period.…”
Section: Physical Exercise and Emotionality In Adhdmentioning
confidence: 96%
“…However, our laboratory historically used 60%*RMT as the conditioning pulse intensity to detect SICI differences in pediatric case-control TMS studies. 19,20 Since this conditioning pulse intensity also elicits significant M1 SICI 29 , we used 60%*RMT for conditioning pulse in this fTMS/S-H task.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13,14 This functional TMS (fTMS) approach requires online TMS measurements while participants are performing behavioral tasks, thus allowing one to probe cortical changes that are state-dependent with high temporal resolution. Providing real-time information on neurophysiologic changes in such a manner broadens the physiologic investigation of motor control 15,16 and neuropsychiatric conditions 17,18,19,20 .…”
Section: Introductionmentioning
confidence: 99%